The G7 Summit: Advancing international climate cooperation? Options and priorities for the German G7 presidency - Susanne Dröge; Marian Feist (Stiftung Wissenschaft und Politik (SWP), 2022)
At the G7 summit in June 2022, the German government intends to promote international climate cooperation by establishing a climate club. This club is envisioned to foster implementation of the Paris climate goals and, ideally, grow into a global alliance of ambitious countries. In light of Russia's attack on Ukraine, energy policy cooperation is now one of the most pressing issues at the G7 summit. Energy security as a short-term priority must be reconciled with accelerated decarbonisation and the international climate agenda. A climate club can certainly provide an impetus for this through agreements on joint regulatory approaches and climate action projects. In terms of the international political process, however, it is important to prevent the initiative from being perceived as a rich countries' club. The German government should carefully manage expectations: Strong signals are needed for COP27 in Egypt in autumn, first and foremost by way of increasing climate finance commitments. Moreover, it will be crucial to shape the G7 club as an ambitious but inclusive initiative.
Keywords: 320